Identification of circular RNAs expression pattern in caprine fetal fibroblast cells exposed to a chronic non-cytotoxic dose of graphene oxide-silver nanoparticle nanocomposites - Yuan, Yu-Guo; Xing, Yi-Tian; Liu, Song-Zi; Li, Ling; Reza, Abu Musa Md Talimur; Cai, He-Qing; Wang, Jia-Lin; Wu, Pengfei; Zhong, Ping; Kong, Il-Keun (Frontiers in Bioengineering and Biotechnology, 2023)
The widespread use of graphene oxide-silver nanoparticle nanocomposites (GO-AgNPs) in biomedical sciences is increasing the chances of human and animal exposure to its chronic non-toxic doses. Exposure to AgNPs-related nanomaterials may result in the negative effect on the dam, fetus and offspring. However, there are only little available information for profound understanding of the epigenetic alteration in the cells and animals caused by low-dose chronic exposure of GO-AgNPs. The present study investigated the effect of 0.5 μg/mL GO-AgNPs for 10 weeks on the differential expression of circular RNAs (circRNAs) in caprine fetal fibroblast cells (CFFCs), and this dose of GO-AgNPs did not affect cell viability and ROS level. We predicted the functions of those differentially expressed (DE) circRNAs in CFFCs by bioinformatics analysis. Furthermore, we validated the expression of ten DE circRNAs using quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR) to ensure the reliability of the sequencing data. Our results showed that the DE circRNAs may potentially regulate the GO-AgNPs-inducing epigenetic toxicity through a regulatory network consisted of circRNAs, miRNAs and messenger RNAs (mRNAs). Therefore, the epigenetics toxicity is essential to assess the biosafety level of GO-AgNPs.